Penerapan Media Wordwall untuk Meningkatkan Hasil Belajar Siswa dalam Materi Unsur Intrinsik Kelas V di SDN 1 Bangodua - Tari Pujiantika Hastuti; Fikriyah Fikriyah; Susilawati Susilawati (CV. ULIL ALBAB CORP, 2024)
Learning at SDN 1 Bangodua teachers use the lecture method, there is a lack of student response, and learning is dominated by teachers who use less technology-based media, which affects learning outcomes in Indonesian language learning. Therefore, learning media has a role in improving learning. One of the media Wordwall can be used to improve learning outcomes. This type of research is classroom action, which is a form of research carried out by teachers to improve the learning process. In this case, the researcher collaborated with the Class V teacher to carry out classroom action research activities on intrinsic elements of Indonesian language learning. Implementation of evaluation using applications Wordwall This aims to provide new experiences for students, the class atmosphere becomes colorful, students become more enthusiastic about learning and taking part in learning evaluations, students also have more courage to come forward to complete the tasks given even though the answers are sometimes not correct, and students understand better. material studied. One of the factors influencing learning outcomes is the media. cycle 1, 59% of students completed, while 41% of students did not complete. With an average learning outcome of 73. Cycle 2 showed that 88% of students had completed the test results, while 12% had not completed it. With an average learning outcome of 85, the research was successful because it exceeded the completion target of 85%. media use Wordwall can improve student learning outcomes.